IMPLEMENTASI PERATURAN BANK INDONESIA (PBI) DALAM KINERJA KEUANGAN PADA BANK MUAMALAT INDONESIA - Desfiandi, Andi (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2015)
One way of performance measurement at syariah financial is by using PBI approach. The purpose of this research is to analyze the level of accounting performance of Muamalat Bank Used Bank Indonesia rules approach with measurement method is CAMEL approach during period of the year 2008 â 2012 Based on the research done at Muamalat Bank in 2008 until 2012 got HEALTH predicate, because CAMEL credit score obtained at 81 above (health minimum standard) was 100 in 2008, 95.63 in 2009, 91.26 in 2010, 100 inÂ 2011 and 100 in 2012.Key words : Health Bank, Capital, Asset, Management, Earning, Liquidity.